Scene complexity: influence on perception, memory, and development in the medial temporal lobe - Chai, Xiaoqian J.; Ofen, Noa; Jacobs, Lucia F.; Gabrieli, John D. (Frontiers in Human Neuroscience, 2010)
Regions in the medial temporal lobe (MTL) and prefrontal cortex (PFC) are involved in memory formation for scenes in both children and adults. The development in children and adolescents of successful memory encoding for scenes has been associated with increased activation in PFC, but not MTL, regions. However, evidence suggests that a functional subregion of the MTL that supports scene perception, located in the parahippocampal gyrus (PHG), goes through a prolonged maturation process. Here we tested the hypothesis that maturation of scene perception supports the development of memory for complex scenes. Scenes were characterized by their levels of complexity defined by the number of unique object categories depicted in the scene. Recognition memory improved with age, in participants ages 8–24, for high-, but not low-, complexity scenes. High-complexity compared to low-complexity scenes activated a network of regions including the posterior PHG. The difference in activations for high- versus low-complexity scenes increased with age in the right posterior PHG. Finally, activations in right posterior PHG were associated with age-related increases in successful memory formation for high-, but not low-, complexity scenes. These results suggest that functional maturation of the right posterior PHG plays a critical role in the development of enduring long-term recollection for high-complexity scenes.